2023
DOI: 10.1519/jsc.0000000000004438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Traditional, Rest Redistribution, and Velocity-Based Prescription on Repeated Sprint Training Performance and Responses in Semiprofessional Athletes

Abstract: Weakley, J, Castilla, AP, Ramos, AG, Banyard, H, Thurlow, F, Edwards, T, Morrison, M, McMahon, E, and Owen, C. The effect of traditional, rest redistribution, and velocity-based prescription on repeated sprint training performance and responses in semi-professional athletes. J Strength Cond Res 37(8): 1566–1572, 2023—The aim of this study was to investigate the effects of traditional, rest redistribution, and velocity-based repeated sprint training methods on repeated sprint performance, perceived effort, hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…At the completion of the training session, subjects immediately completed a CMJ and then waited, passively, for 15 minutes. Following this standardized 15-minute period, subjects were asked to provide a differential rating of perceived exertion for breathlessness (RPE-B) and exertion of the lower peripheries (RPE-L) (27,32). Finally, TMG assessment of the vastus lateralis and the 10 m sprint were repeated which took approximately 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…At the completion of the training session, subjects immediately completed a CMJ and then waited, passively, for 15 minutes. Following this standardized 15-minute period, subjects were asked to provide a differential rating of perceived exertion for breathlessness (RPE-B) and exertion of the lower peripheries (RPE-L) (27,32). Finally, TMG assessment of the vastus lateralis and the 10 m sprint were repeated which took approximately 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The significance level was set at α = 0.05 and the power at 0.80. This analysis estimated that the minimum sample size required per group in a twosample t-test scenario would be 19 participants [22,37,39,56]. However, due to constraints in available resources and the high specificity of the elite athlete population targeted in our study, a smaller sample size was deemed necessary and acceptable.…”
Section: Participantsmentioning
confidence: 99%
“…Adaptation to these short rest intervals between sprints can enhance recovery mechanisms and the activity of enzymes involved in both aerobic and anaerobic energy production [19]. Therefore, coaches may attempt to reduce rest intervals or increase training volume to achieve high intensities, but this approach could lead to exhaustion, and adversely affect sprint mechanics [14,17,[20][21][22][23][24]. Moreover, while players and coaches often expect this training to enhance explosive acceleration from the start (0-20 m), research has revealed that it works best at 20-30 m [15,18,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations